2015
DOI: 10.1080/21580103.2015.1044024
|View full text |Cite
|
Sign up to set email alerts
|

Mixed heavy metal stress on photosynthesis, transpiration rate, and chlorophyll content in poplar hybrids

Abstract: The present work aimed to study the physiological effects of mixed heavy metals, cadmium (Cd), copper (Cu), chromium (Cr), and zinc (Zn) in four poplar hybrids. Poplar hybrids were treated once with six different concentrations (0, 5, 50, 100, 200, and 500 ppm) of mixed heavy metals for a period of 3 months. The photosynthetic and transpiration rates were measured before and during treatment using an LCiÀSD portable photosynthesis system whereas the photosynthetic pigments were analytically determined. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 13 publications
7
69
0
Order By: Relevance
“…Similarly, Pajević et al (2009) showed that A and E were significantly decreased in most of the Populus and Salix clones exposed to Pb, Cd, Ni. In addition, the reduction of A, E, g s in different poplar clones under heavy metal stress has been reported by Gu et al (2007), Pietrini et al (2010), and Chandra and Kang (2015). The inhibition of plant photosynthetic parameters under heavy metal stress results in damage to photosynthetic enzymes and chloroplast membranes, decrease in chlorophyll synthesis, replacement of heavy metals in the chlorophyll molecule, accumulation of heavy metals in the photosynthetic organs of plants (leaves) and interference of metal ions with the uptake of essential elements of the photosynthetic process (Chandra, Kang 2015).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, Pajević et al (2009) showed that A and E were significantly decreased in most of the Populus and Salix clones exposed to Pb, Cd, Ni. In addition, the reduction of A, E, g s in different poplar clones under heavy metal stress has been reported by Gu et al (2007), Pietrini et al (2010), and Chandra and Kang (2015). The inhibition of plant photosynthetic parameters under heavy metal stress results in damage to photosynthetic enzymes and chloroplast membranes, decrease in chlorophyll synthesis, replacement of heavy metals in the chlorophyll molecule, accumulation of heavy metals in the photosynthetic organs of plants (leaves) and interference of metal ions with the uptake of essential elements of the photosynthetic process (Chandra, Kang 2015).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Pajević et al (2009) demonstrated that photosynthesis and transpiration in most of the studied Populus Linnaeus and Salix Linnaeus clones exposed to Pb, Cd and Ni decreased significantly. Also, the decline in gas exchange parameters of different poplar clones in response to heavy metal stress has been shown by Gu et al (2007), Pietrini et al (2010), and Chandra and Kang (2015). On the other hand, He et al (2013) showed that while Cd exposure caused a decline in the photosynthesis of four poplar species (Populus alba Linnaeus × Populus glandulosa Ueki, Populus euramericana (Dode) Guinier, Populus cathayana Rehder, and Populus deltoides Bartram ex Marshall), no change was observed on Populus nigra Linnaeus and Populus popularis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, excess of any kind of metal adversely affects plant metabolism and growth rate (Hall, 2002;Chandra and Kang, 2016). Stomata aperture is strongly regulated by divergent exogenous stimuli, such as light, drought stress, pathogens, temperature and others (Acharya and Assmann, 2009).…”
Section: Design Of Phytoremediation Experimentsmentioning
confidence: 99%